The impact of technological innovations on financial deepening: Implications for SME financing in Africa. - Sanga, Bahati; Aziakpono, Meshach (African Development Review / Revue Africaine de Développement, 2022)
This paper examines whether technological innovations such as information and communication technology infrastructure, mobile phone subscriptions, secure internet servers and the number of automated teller machines and bank branches increased financial deepening in 43 African countries for the period 2010–2019. The study employs panel corrected standard errors, fixed effects and quantile regressions for empirical analysis. The results show that technological innovations have a positive and significant influence on financial deepening in Africa in terms of banks' mobilisation of deposits and allocation of credit to enterprises. Furthermore, the technological indicators have a strong and positive effect on higher levels of bank credit to the private sector than lower levels. As for bank deposits, only the number of branches was found to have significant and positive effects at a high level of bank deposits compared with a low level. These results imply that African governments and development partners can leverage ICT developments to increase financial deepening and reinvigorate debt financing, which is the primary funding source for small and medium‐size enterprises.